2014
DOI: 10.1007/s12522-014-0189-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of signaling pathways on proliferation and self‐renewal of cultured bovine primitive germ cells

Abstract: These results indicate activation of MAPK plays a critical role in self-renewal and survival of bovine gonocytes via cyclin D1 and CDK2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
1
6
0
1
Order By: Relevance
“…The established cell lines from immature testes had mouse ES cell‐like morphology in serum‐free medium supplemented with GDNF and bLIF, and they expressed both germ‐cell‐specific ( UCHL‐1 and DBA ) and pluripotent stem cell markers ( OCT4 , SOX2 , KLF4 ). Consistent with our results, other studies have reported that in vitro culture of gonocytes from neonatal bovine testes yields ES cell‐like colonies (Sahare et al, ) that express cell surface markers of ES cells (Li et al, ). In contrast, isolated undifferentiated spermatogonia from adult testes could be maintained in the medium only in the presence of BIO and formed colonies with botryoidally aggregated cell morphology, similar to typical mouse GS cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The established cell lines from immature testes had mouse ES cell‐like morphology in serum‐free medium supplemented with GDNF and bLIF, and they expressed both germ‐cell‐specific ( UCHL‐1 and DBA ) and pluripotent stem cell markers ( OCT4 , SOX2 , KLF4 ). Consistent with our results, other studies have reported that in vitro culture of gonocytes from neonatal bovine testes yields ES cell‐like colonies (Sahare et al, ) that express cell surface markers of ES cells (Li et al, ). In contrast, isolated undifferentiated spermatogonia from adult testes could be maintained in the medium only in the presence of BIO and formed colonies with botryoidally aggregated cell morphology, similar to typical mouse GS cells.…”
Section: Discussionsupporting
confidence: 92%
“…GDNF is produced by Sertoli cells and supports mouse SSC proliferation in vivo (Meng et al, ) and in vitro (Hasegawa, Namekawa, & Saga, ). In cattle, the addition of GDNF to culture medium activates the mitogen‐activated protein kinase (MAPK) signaling pathway and supports long‐term proliferation of gonocyte isolated from neonatal and immature testes (Sahare et al, ). However, when the neonatal culture system was applied to culture adult bovine spermatogonia, they could not be maintained for a long time (Fujihara et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that mouse and cattle germ cells need different factors for cell growth. Similarly, our previous findings reveal that mitogenactivated protein kinase (MAPK) signalling plays a crucial role in maintaining self-renewal and colony formation of bovine gonocytes in culture, whereas cultured mouse germ cells require the crosstalk between MAPK and phosphoinositide 3-kinase (PI3K) signalling pathways for self-renewal (Sahare et al 2015). These different signalling pathways are activated under the influence of different growth factors.…”
Section: Discussionmentioning
confidence: 83%
“…However, no long‐term culture system for livestock species has been developed. In the authors’ laboratory, growth factors, matrix substrates for culture dishes, and serum‐free supplements have been examined in order to develop a defined system for culturing primitive GCs (gonocytes) from the neonatal bovine testis . Poly‐L‐lysine is a suitable substrate for the selective inhibition of the growth of somatic cells and makes it possible to maintain gonocytes.…”
Section: In Vitro Culture Of the Spermatogonial Stem Cellsmentioning
confidence: 99%